A model study on the site-specificity of (−)-epicatechin-induced reactions in β-lactoglobulin by high-resolution mass spectrometry in combination with bioinformatics. (15th May 2023) - Börsig, Amelie; Konar, Nevzat; Dalabasmaz, Sevim
Highlights: Polyphenol–protein reactions between β-lactoglobulin (β-LG) and (−)-epicatechin. Addition of epicatechin altered the tryptic peptide profiles of β-LG models. Site-specificity of (−)-epicatechin o -quinones were determined. Covalent reactions were determined at S27, S30, K60, C66, K69, and C160. (−)-Epicatechin promoted the formation of methionine sulfoxide. Abstract: Polyphenol–protein reactions in model solutions of β-lactoglobulin (β-LG) incubated with (−)-epicatechin at 37 °C and 60 °C were monitored by microLC–timsTOF Pro-MS/MS combined with bioinformatics strategies. The addition of (−)-epicatechin to the model solutions resulted in changes in tryptic peptide profiles. Covalent bond formation between (−)-epicatechin o -quinones and β-LG was identified for the residues S27, S30, K60, C66, K69, and C160, with C160 being the predominant binding site. Furthermore, the incubation of β-LG with (−)-epicatechin significantly promoted oxidation, especially for the residues M7 and M24. The reaction of monomeric (−)-epicatechin  o -quinone at C160 was also identified in the milk chocolate sample. The adaptation of this study by extending the scope of the reaction products offers significant potential for comprehensive food profiling strategies.